Lack of July effect in the utilization of neuraxial and peripheral nerve block in US teaching hospitals: a retrospective analysis. Issue 5 (24th March 2020) - Kim, Sang Jo; Wilson, Lauren; Liu, Jiabin; Kim, David H; Fiasconaro, Megan; Poeran, Jashvant; Freeman, Carrie; Beathe, Jonathan; Memtsoudis, Stavros
Abstract : Background: Given the steep learning curve for neuraxial and peripheral nerve blocks, utilization of general anesthesia may increase as new house staff begin their residency programs. We sought to determine whether "July effect" affects the utilization of neuraxial anesthesia, peripheral nerve blocks, and opioid prescribing for lower extremity total joint arthroplasties (TJA) in July compared with June in teaching and non-teaching hospitals. Methods: Neuraxial anesthesia, peripheral nerve block use, and opioid prescribing trends were assessed using the Premier database (2006–2016). Analyses were conducted separately for teaching and non-teaching hospitals. Differences in proportions were evaluated via χ 2 test, while differences in opioid prescribing were analyzed via Wilcoxon rank-sum tests. Results: A total of 1 723 256 TJA procedures were identified. The overall proportion of neuraxial anesthesia use in teaching hospitals was 14.4% in both June and July (p=0.940). No significant changes in neuraxial use were seen in non-teaching hospitals (24.5% vs 24.9%; p=0.052). Peripheral nerve block utilization rates did not differ in both teaching (15.4% vs 15.3%; p=0.714) and non-teaching hospitals (10.7% vs 10.5%; p=0.323). Overall median opioid prescribing at teaching hospitals changed modestly from 262.5 oral morphine equivalents (OME) in June to 260 in July (p=0.026) while median opioid prescribing remained at a constant value of 255 OME at non-teaching hospitals (p=0.893). Conclusion: Utilization of neuraxial and regional anesthesia techniques was not affected during the initial transition period of new house staff in US teaching institutions. It is feasible that enough resources are available in the system to accommodate periods of turnover and maintain levels of regional anesthetic care including additional attending anesthesiologist oversight.